Controllable synthesis of small size CsxWO3 nanorods as transparent heat insulation film additives. Issue 11 (20th February 2018) - Liu, Jingxiao; Chen, Bin; Fan, Chuanyan; Shi, Fei; Ran, Shuai; Yang, Jingyuan; Song, Xin; Liu, Su-Hua
Abstract : Small size Cs x WO3 nanorods synthesized using pure ethanol as the solvent exhibited the best visible transparency and NIR shielding performance. Abstract : To achieve simultaneously higher transparency and heat-shielding performance of Cs x WO3 for energy-saving glass applications, we developed small size Cs x WO3 nanorods with lengths of 10–60 nm by controllable solvothermal reaction and a subsequent heat-treatment with citric acid thermolysis under a N2 atmosphere. It has been proved that crystal growth could be controlled by using solid state gel-like tungstic acid as the W source and controlling the water content in the precursor solution. In the meantime, the deposited carbon film on the particle surface due to thermolysis of citric acid during N2 heat-treatment could also inhibit the crystal growth. It has been confirmed that the as-prepared Cs x WO3 films on a glass substrate from dispersion of Cs x WO3 particles after N2 heat-treatment with citric acid thermolysis exhibited improved transparency and near-infrared (NIR) shielding ability. Particularly, the Cs x WO3 particles synthesized using pure ethanol as the solvent exhibited the best visible light transparency and NIR shielding performance. The mechanism of controlling the small size and improving the visible light transparency and NIR shielding ability of Cs x WO3 particles was discussed, which is of significance for realizing broad applications in the field of energy-saving glasses, and the synthetic strategy is also suitable for synthesizing other small size functional nanoparticles.